Thin Layer Chromatography of Phenols on Anilinium Iron (III) Phosphate-Silica Gel G - Singh, D.K.; Srivastava, Bhavana (Asian Journal of Chemistry, 2010)
The use of anilinium iron (III) phosphate (AIP) silica gel G (SG) in thin layer chromatography of 22 phenols has been investigated. The effects of AIP-SG ratio and electrolytes (eluents) on hRF values have been studied. Some analytically important binary and ternary separations on AIP : SG (1 : 5) thin layers have been achieved.